Exploring collaborative reverse subtitling for the enhancement of written production activities in English as a second language. Issue 1 (19th October 2016) - Talaván, Noa; Ibáñez, Ana; Bárcena, Elena
Abstract: This article explores the effects of collaborative reverse subtitling as an activity for the promotion of writing skills in English as a second language. An initial analysis is undertaken of the pros and cons of the role of translation in second language learning historically and the role of information and communication technology in this process, with special attention being paid to recent initiatives on the didactic use of audiovisual translation in the form of subtitling, and the evidence of their efficacy obtained so far. Subsequently, a completed research project is described, which was aimed at promoting second language learning among distance learning university students through collaborative reverse subtitling. Specifically, the project aimed to explore both the potential of a guided subtitling activity for the development of written production skills, and also the dynamics of undertaking such an activity collaboratively, in order to gain insights on the social, cognitive, metacognitive and transfer mechanisms that can be activated in collective study. Finally, we reflect on the need to accumulate evidence on multimodal translating scenarios combining individual and collective work for the development of communicative language competences, through further research and classroom use, in order to consolidate and refine these findings.